The commission of the peace, 1675-1720 - Glassey, L (1973)
In the period from 1675 to 1720, the Justices of the peace in the English and Welsh counties were appointed by royal authority delegated to the Lord Chancellor. The Chancellor thus possessed a formidable instrument of patronage, which he operated both by power of appointment and by power of dismissal. This patronage extended principally to a class of persons of considerable influence within the political nation of the seventeenth and eighteenth centuries, that is, the country gentry. It has long been surmised that, within the period under review, the local patronage of the Chancellor was employed to secure political advantage. Such a purpose might be defensive, to safeguard the state against those not wholly committed to the Anglican Church, the principles of the Revolution of 1688, or the Hanoverian Succession; or it might be aggressive, to reward friends with, and deprive enemies a local authority which it was generally thought to be both honourable and desirable to exercise. The commission of the peace was thus a means by which changes in central policy, and shifts in central power, were extended into the localities. In a period when Parliamentary and electoral politics, and, to a lesser but still important extent, ministerial politics, became influenced by distinctions of party, it is a reasonable hypothesis that local politics became similarly influenced through the medium of appointments to the local magistracy. The object of this study has been to confirm or deny this hypothesis. To do so, it is necessary to measure how widespread the regulations of the county commissions of the peace were; there were fifty-five counties, one county palatine, and two liberties analagous to counties (besides several small liberties and corporations) for which separate commissions of the peace were issued. Substantial changes in any one of these might attract attention from contemporaries of a kind which would give a possibly misleading impression that similar changes took place in other counties as well. It is also necessary to measure the relative scale of the alterations that were made. The bench of magistrates varied in size in different counties at the same time and in the same county at different times. The commission of the peace for a given county could be remodelled by adding names to the list of gentlemen who were empowered to act as justices, or by omitting names from it. Such remodelling can only be put in perspective in the context of the total length of the list at the time that the regulation took place, furthermore, it is of importance to ascertain the precise timing of changes in the commissions, in order to judge how far such changes originated in changes at the centre of politics, and how far the changes at the local level themselves resulted in political consequences of wider significance, in, for instance, general elections. [See pdf. for full abstract]